Contrafreeloading in the Domestic Dog (Canis lupus familiaris) - Rothkoff, Liza (CUNY Academic Works, 2023)
Contrafreeloading is the behavior of working for food that requires effort to obtain when also provided with food that does not require effort to obtain. More specifically, contrafreeloading can be defined in multiple ways using various criterion such as 1) an animal’s preference and/or 2) an animal’s willingness to work for food when freely available food is offered. To date, multiple studies have evaluated contrafreeloading in various animal species, identifying that many non-domesticated species (e.g., maned wolves, red jungle fowl) and domesticated species (e.g., pigs, goats) demonstrate a preference and/or a willingness to work for food when readily available food is present. Most recently, Delgado et al., (2021) observed that domestic cats prefer freely available food over food that requires effort. In an adaptation of this research, we assessed whether another domesticated companion animal, dogs, contrafreeload when presented with two feeders simultaneously, a food puzzle (snuffle mat) and a tray. Thirty-eight pet dogs participated in the study in which they were presented with 10 feeding trials where food was distributed equally in both feeders. All dogs wore activity trackers for the duration of the study and feeding trials were video-recorded and behaviorally analyzed for first approaches to each feeder and time spent at each feeder. We also accounted for food eaten at each feeder. Overall, we did not find evidence of preference to contrafreeload behavior in domestic dogs, however we did find evidence of a willingness to contrafreeload. Dogs approached the tray before the snuffle mat most often. Willingness to contrafreeload was significantly correlated with owner reported body condition score (r (36) = 0.337, p = 0.039) but not activity level (r (34) = -0.259, p = 0.051). Our results could inform future recommendations for pet dog enrichment.